The Risk Transfer among Exchange Rates, Energy Commodities, and Agricultural Commodity Prices in SADC Countries - Vuba, Nonelelo; Qabhobho, Thobekile (International Journal of Energy Economics and Policy, 2024)
This paper investigates the risk transfer between exchange rates, energy commodities, and agricultural commodity prices in SADC nations from July 29, 2007, to December 18, 2022. The Time-varying parameter Vector Autoregression connectivity technique is specifically used. The total connectivity index for the specific network of energy commodities, currency rates, and agricultural commodities is 24.39%. The energy commodities index (crude oil and heating oil) and the ZAR were the largest shock transmitters, according to averaged dynamic connectedness. In contrast, two SADC currency markets (MWK and MZN), natural gas, and corn were net shock recipients. Furthermore, overall connection indices were shown to change dramatically with high sensitivity to crisis events, particularly the 2007/2008 crisis and the COVID-19 pandemic. As indicated by net directional connection, most energy commodities, as well as the Rand and the Pula, were persistent net transmitters over time. This is especially noteworthy given oil's direct impact on agricultural commodities. The findings of this paper are useful for policymakers who are attempting to maximize public benefit. Policymakers charged with developing policies for economically vulnerable segments of the population should use these findings to examine the potential impact of changes in energy prices on food and currency markets.